2009
DOI: 10.1007/s10096-009-0803-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital

Abstract: The antimicrobial stewardship program (ASP) is a major strategy to combat antimicrobial resistance and to limit its expenditure. We have improved on our existing ASP to implement a sustainable and cost-effective two-stage immediate concurrent feedback (ICF) model, in which the antimicrobial prescription is audited by two part-time infection control nurses at the first stage, followed by "physician ICF" at the second stage. In January 2005, an ASP focused on broad-spectrum intravenous antibiotics was implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…In view of these patients' immunocompromised status, physicians are often reluctant to discontinue antibiotics after an optimal duration of therapy or de-escalate therapy when susceptible microorganisms are cultured [3]. Few published studies have addressed the role of antimicrobial stewardship specifically in this patient population [4][5][6], yet, the opportunities for providing guidance on the judicious prescription of antibiotics are arguably greater compared to most other patient populations and settings.…”
Section: Introductionmentioning
confidence: 93%
“…In view of these patients' immunocompromised status, physicians are often reluctant to discontinue antibiotics after an optimal duration of therapy or de-escalate therapy when susceptible microorganisms are cultured [3]. Few published studies have addressed the role of antimicrobial stewardship specifically in this patient population [4][5][6], yet, the opportunities for providing guidance on the judicious prescription of antibiotics are arguably greater compared to most other patient populations and settings.…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies have demonstrated that strategies involving prospective audit with intervention and feedback can improve antibiotic stewardship, as measured by reductions in inappropriate antibiotic use, 30 reduced antibiotic costs or overall consumption, [31][32][33][34][35] greater compliance with hospital treatment guidelines or policies 33,36,37 and, in some cases, reduced number of infections due to C difficile infection 32,37 or resistant pathogens. 31,32,37 Prospective audit with feedback is probably the best and most effective core strategy for a community hospital program where other interventions are cumbersome or not as well tolerated by the medical staff.…”
Section: Prospective Audit With Intervention and Feedbackmentioning
confidence: 99%
“…Some facilities restrict the use of certain antibiotics based on the spectrum of activity, cost, or associated toxicities to ensure the use is reviewed with an antibiotic expert. There is sufficient scientific evidence to support improvement in clinical outcome as a consequence of antibiotic stewardship program; the measures include curtailing the antibiotic abuse [5], decreased antimicrobial consumption [6], strict antibiotic usage guidelines [6,7], reduced length of hospital stay [8], improved ventilator-acquired pneumonia outcomes [9], and better patient outcomes with infection [5].…”
Section: Editorialsmentioning
confidence: 99%
“…A recent multi-centric study conducted by the Indian Council of Medical Research (ICMR) has revealed that CAH is not uncommon, especially in South India with a reported prevalence of a little over 1 in 2000 [6]. With newborn screening for congenital hypothyroidism yet to pick up in a big way in India, screening for CAH with standardized 17-hydroxy-progesterone assay still has a long way to go.…”
mentioning
confidence: 99%